Internalisasi Nilai Aklaqul Karimah Siswa MI Tarbiyatut Tholabah Kranji Paciran Lamongan - Hakim, Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of education is to change from those who do not know to know, educate people's lives, improve welfare, have high social attitudes, have noble character, are skilled, capable, creative, knowledgeable, become democratic, independent, responsible and pious citizens. to God Almighty. This study uses a descriptive qualitative approach and data collection techniques through observation, interviews, documentation and socialization. Meanwhile, the data analysis uses data reduction to describe the Internalization of Moral Values ​​for Students at MI Tarbiyatut Tholabah Kranji, Paciran, Lamongan. The purpose of the study was to provide students with an understanding of the urgency of morality, both to Allah, parents, teachers, peers and morality to others related to students' daily lives. This study also has the aim of analyzing how the level of morality of students is considered as a material for assessing the moral quality of students who are the next generation of the Indonesian nation now or in the future. This research resulted that students were very enthusiastic and participated high enough to become better human beings, this was proven implicitly in the socialization activities that had been carried out, which impliedly showed that the moral development of students was getting better in respecting others.